Corporate Social Responsibility of Islamic Bank: Enhancing Customer Trust, Corporate Reputation, and Customer Loyalty - Putri, Nabiilah Aatika; Hasib, Fatin Fadhilah (BISNIS, 2024)
Islamic banking faces challenges competing with conventional banking, particularly regarding market share. To address this challenge, Islamic banks must strengthen customer relationships for long-term sustainability. This research aims to examine whether customer trust and reputation mediate the effect of CSR on customer loyalty in Bank Syariah Indonesia (BSI). The study employed a quantitative approach with the SEM-PLS analysis technique. The sampling method was simple random sampling, with 170 respondents participating in an online questionnaire. The findings of this study suggest that CSR does not have a direct impact on Customer Loyalty. However, mediation through Customer Trust and Corporate Reputation is crucial. The results reveal that customers’ decisions to be loyal to Bank Syariah Indonesia (BSI) are not directly influenced by the observable CSR activities; instead, customer trust and corporate reputation play vital roles in mediating the effects of CSR on customer loyalty. This study implies that Bank Syariah Indonesia (BSI) needs to emphasize the significance of customer trust by enhancing service quality. Furthermore, building a positive reputation for the customers by disseminating adequate information regarding Sharia financial products is equally imperative.